Development Real-Time PCR Assays to Genetically Differentiate Vaccinated Pigs From Infected Pigs With the Eurasian Strain of African Swine Fever Virus - Velazquez-Salinas, Lauro; Ramirez-Medina, Elizabeth; Rai, Ayushi; Pruitt, Sarah; Vuono, Elizabeth A.; Espinoza, Nallely; Gladue, Douglas P.; Borca, Manuel V. (Frontiers in Veterinary Science, 2021)
Currently, African swine fever virus (ASFV) represents one of the most important economic threats for the global pork industry. Recently, significant advances have been made in the development of potential vaccine candidates to protect pigs against this virus. We have previously developed attenuated vaccine candidates by deleting critical viral genes associated with virulence. Here, we present the development of the accompanying genetic tests to discriminate between infected and vaccinated animals (DIVA), a necessity during an ASFV vaccination campaign. We describe here the development of three independent real-time polymerase chain reaction (qPCR) assays that detect the presence of MGF-360-12L, UK, and I177L genes, which were previously deleted from the highly virulent Georgia strain of ASFV to produce the three recombinant live attenuated vaccine candidates. When compared with the diagnostic reference qPCR that detects the p72 gene, all assays demonstrated comparable levels of sensitivity, specificity, and efficiency of amplification to detect presence/absence of the ASFV Georgia 2007/1 strain (prototype virus of the Eurasian lineage) from a panel of blood samples from naïve, vaccinated, and infected pigs. Collectively, the results of this study demonstrate the potential of these real-time PCR assays to be used as genetic DIVA tests, supporting vaccination campaigns associated with the use of ASFV-MGF, ASFV-G-9GL/∆UK and ASFV-I177L or cell culture adapted ASFV-I177L∆LVR live attenuated vaccines in the field.